2014
DOI: 10.1007/s00792-014-0680-7
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and phylogenetic diversity of thermophilic cyanobacteria in Algerian hot springs

Abstract: Geothermal springs in Algeria have been known since the Roman Empire. They mainly locate in Eastern Algeria and are inhabited by thermophilic organisms, which include cyanobacteria forming mats and concretions. In this work, we have investigated the cyanobacterial diversity of these springs. Cyanobacteria were collected from water, concretions and mats in nine hot springs with water temperatures ranging from 39 to 93 °C. Samples were collected for isolation in culture, microscopic morphological examination, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 40 publications
1
28
0
2
Order By: Relevance
“…G. lithophora and T. elongatus lineages in many biotopes around the world including carbonate rocks from several Mexican lakes, karstic areas and thermophilic or hypersaline microbial mats collected in South America and Europe. Amarouche-Yala et al [28] also found 16S rDNA sequences phylogenetically close to Ca. G. lithophora in hot springs in Algeria.…”
Section: Introductionmentioning
confidence: 91%
“…G. lithophora and T. elongatus lineages in many biotopes around the world including carbonate rocks from several Mexican lakes, karstic areas and thermophilic or hypersaline microbial mats collected in South America and Europe. Amarouche-Yala et al [28] also found 16S rDNA sequences phylogenetically close to Ca. G. lithophora in hot springs in Algeria.…”
Section: Introductionmentioning
confidence: 91%
“…Cyanobacteria, the oxygen evolving photosynthetic prokaryotes, are ubiquitous in nature and found all over the world encompassing ice continents of Arctic and Antarctic (Vezina and Vincent 1997) to hot spring, where the temperature is near 70°C (Amarouche-Yala et al 2014). Freezing temperatures accompanied by freeze-cycles, extreme fluctuation in UV irradiance, and low availability of nitrogen are major problems in polar regions hampering the growth of cyanobacteria (Grzesiak et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Cyanobacterial diazotrophs play a significant role in nutrient cycling by their inherent ability to fix atmospheric nitrogen and carbon (Saha et al 2007;Prabaharan et al 2010). Cyanobacteria fixes atmospheric nitrogen in different thermal extremes, including Antarctic, where the temperature is always below 0°C (Priscu et al 1998), in an arid desert (Winckelmann et al 2015) and in hot spring where the temperature ranges from 55 to 70°C (Amarouche-Yala et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…PCR amplification of the 16S rRNA plus the internal transcribed spacer (ITS) region was performed in 25‐μl (final volume) reaction mixture containing 12.5 μl of the EmeraldAmp Max PCR Master Mix premix (TaKaRa Bio, Otsu, Japan) provided with polymerase, optimized buffer, MgCl2, and dNTP mix (composition is proprietary), 1 μl of each of the primer (20 μM), 2 μl of the template DNA and ddH2O. Specific primers CYA106F (5′‐CGG ACG GGT GAG TAA CGC GTG A‐3′) and 23S0R (5′‐CTT CGC CTC TGT GTG CCT AGG T‐3′) amplifying cyanobacterial 16S rRNA plus adjacent ITS were used in the study (Amarouche‐Yala, Benouadah, El Ouahab Bentabet, & López‐García, ). PCR conditions were as follows: 94°C for 2 min; 35 cycles at 94°C for 15 s, 55°C for 30 s, and 72°C for 2 min; final extension at 72°C for 7 min (Amarouche‐Yala et al, ).…”
Section: Methodsmentioning
confidence: 99%